2016
DOI: 10.1177/1457496915626834
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Vertebral Bone Defects using an Expandable Replacement Device and Bioactive Glass S53P4 in the Treatment of Vertebral Osteomyelitis: Three Patients and Three Pathogens

Abstract: Background and Aims: bioactive glass s53p4 is an antibacterial bone substitute with bone-bonding and osteostimulative properties. the bone substitute has been successfully used clinically in spine; trauma; orthopedic; ear, nose, and throat; and cranio-maxillofacial surgeries. bioactive glass s53p4 significantly reduces the amount of bacteria in vitro and possesses the capacity to kill both planktonic bacteria and bacteria in biofilm. three patients with severe spondylodiscitis caused by Mycobacterium tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…BAG S53P4 has been studied clinically in randomised prospective trials in bone tumour [27,28], trauma [29] and spine surgery [30,31]. Due to its antibacterial properties is has also been used in the treatment of severe chronic osteomyelitis, mastoiditis, spine infections and frontal sinus infections [21,[32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…BAG S53P4 has been studied clinically in randomised prospective trials in bone tumour [27,28], trauma [29] and spine surgery [30,31]. Due to its antibacterial properties is has also been used in the treatment of severe chronic osteomyelitis, mastoiditis, spine infections and frontal sinus infections [21,[32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Although conservative treatment may allow satisfactory bone healing in some cases, surgical management is indispensably essential, specifically in the severe cases of critical-sized or large bony defect and in vertebral osteomyelitis. Alternative treatment strategy and approach using different bioartificial graft substitutes and materials need to be developed and discovered since the standard procedure using autologous bone grafts was associated with major drawbacks [ 2 , 5 , 6 ]. In this study, we evaluated the outcome of umbilical cord mesenchymal stem cell application combined with hydroxyapatite-based scaffolds (Bongros®) in the treatment of vertebral bone defect due to spondylitis tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no bacterial resistance to S53P4 bioactive glass has been reported and Drago et al showed that S53P4 bioactive glass is even active against multidrug resistant bacterial strains 39,40 . There is also some very preliminary data on activity of S53P4 bioactive glass against Candida albicans, a fungus responsible for some bone infections 41,42 . Interestingly, both mechanisms are detrimental for prokaryotic structures, like bacteria, but not so for eukaryotic cells 43,44 …”
Section: Cierny Stage III and Iv Osteomyelitismentioning
confidence: 99%
“…39,40 There is also some very preliminary data on activity of S53P4 bioactive glass against Candida albicans, a fungus responsible for some bone infections. 41,42 Interestingly, both mechanisms are detrimental for prokaryotic structures, like bacteria, but not so for eukaryotic cells. 43,44 The Tissue response towards the material is also enhanced when compared to hydroxyapatite alone.…”
Section: Cierny Stage III and Iv Osteomyelitismentioning
confidence: 99%